APPLICATION OF MASTERING CONTENT SERVICES TO INCREASE MATHEMATIC ACHIEVEMENT OF STUDENT AT CLASS VII SMP NEGERI 2 METRO YEAR 2013/2014 - Mahmudah, Siti (Universitas Muhammadiyah Metro, 2016)
Goals to be achieved by the researchers, is to know the results of the implementation of the mastery content services in improving student achievement of class VII SMP Negeri 2 Metro in the academic year 2013/2014. The study design using action research applied in guidance and counseling services. Subjects in this study, researchers took student class VII SMP Negeri 2 Metro in the academic year 2013/2014. Of the 24 students there are 10 students who experienced low mathematics achievement 41.66%. Results from this study that through mastery of content services provided by BK teachers can improve student achievement class VII SMP Negeri 2 Metro. There is an increase in student achievement in the first cycle seen from the average percentage that is equal to 27.5% and the second cycle by 75%, resulting in an increase of 47.5%.Keywords: mathematics achievement, mastery content services, smp negeri 2 metro